THE EFFECT OF AUDIO-VISUAL MEDIA ON DIGESTIVE SYSTEM MATERIAL CONCEPT IN VIII CLASS - Yustina Hapida; Syarifah Syarifah; Ummi Hiras Habisukan; Vivi Weliyani (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
This study aims to determine the effect of audio visual use on students' mastery concepts. The type of research is quasi experiment . The design of this research is Non-equivalent Control Group Design. The population of this study are students of class VIII SMP. The sample of this research VIII.A class as experimental class and VIII.B class as control class chosen by purposive sampling. In the learning process, the experimental class is taught by using Audio visual media in the form of video and control class is taught with power point media (PPT). Data retrieval uses conception master test with multiple choice form which has been tested for its validity and reliability. Quantitative data were obtained from the average pretest, posttest, and N-gain values analyzed using t-test. Result of research of hypothesis test of Posttest data shows that value of Sig = 0,037 <0,05. While the value of t-arithmetic = 2, 152> t-table = 1.684. The average value of N-gain Pretest-Posttest experimental class is 0.67 classified, while the average value of N-gain Pretest-Posttest control class is 0.57 including medium category. Based on the results of the study can be concluded that the application of audio visual media in the form of video significantly influence the mastery of students' concepts on the material of human digestive system in VIII class. Keywords: concept mastery, digestive system, learning, audio visual media